Haloperidol-Midazolam vs. Haloperidol-Ketamine in Controlling the Agitation of Delirious Patients; a Randomized Clinical Trial - Aghili, Mehrad; AkhavanHejazi, Hamidreza; Naderpour, Zeinab; Vahidi, Elnaz; Saeedi, Morteza (Archives of Academic Emergency Medicine, 2023)
Introduction: Agitation management in delirious patients is crucial in a crowded emergency department (ED) for both patient and personnel safety. Benzodiazepines, antipsychotics, and newly derived ketamine are among the most commonly used drugs in controlling these cases. This study aimed to compare the effectiveness of haloperidol-midazolam with haloperidol-ketamine combination in this regard. Methods: In this double-blind randomized clinical trial, delirious patients with agitation in ED were randomly assigned to a group: group A: haloperidol 2.5 mg IV and midazolam 0.05 mg/kg IV or group B: haloperidol 2.5 mg IV and ketamine 0.5 mg/kg IV. Sedative effects as well as side effects at 0, 5, 10, 15, 30 minutes and 1, 2, 4 hours after the intervention were compared between the 2 groups. Results: We enrolled 140 cases with Altered Mental Status Score (AMSS)≥+2 and mean age of 52.8±19.4 years (78.5% male). Agitation was significantly controlled in both groups (p<0.05). In group B, AMSS score was more significantly and rapidly reduced 5 (p = 0.021), 10 (p = 0.009), and 15 (p = 0.034) minutes after drug administration. After intervention, oxygen saturation was significantly decreased in group A 5 (p = 0.031) and 10 (p = 0.019) minutes after baseline. Time required to the maximum effect was significantly lower in group B versus group A (p=0.014). Less patients in group B had major side effects (p=0.018) and needed physical restraint (p=0.001). Conclusions: Haloperidol-ketamine can control agitation in delirium more rapidly than haloperidol-midazolam. This combination had lower adverse events with lower need for physical restraint.